Effect target variation on accuracy smash - Husaini Husaini; Eka Supriatna; Edi Purnomo (Universitas Sriwijaya, 2022)
This research focuses on improving skills in volleyball smash techniques. In the brojo club, there must be some athletes who must improve their smash and the direction or target to be aimed, based on that the researcher wants to provide a solution by using a variety of target training in the hope of getting good results so that it can be applied in the training process. This research uses One-Group Pretest-Posttest Design. The population in this study were 10 male athletes of the Brojo Musti Club. The instrument used in this study was a smash test, each athlete smashed 10 times and there were scores or numbers in each corner of the field. The results of the research conducted, there is an influence on smash accuracy skills from the protest and posttest data. Results of the t-test calculations, T = 9.05 is greater than T-table = 2.26. So could be concluded that that the treatment effect of target variations influences smash accuracy. To determine the percentage of influence, the calculation of the percentage of influence obtained is 80%.